The Role of Organizational Culture in Tackling Stunting in Indonesia - Isa Mulatif; Des Hanafi (Marasofi International Media and Publishing (MIMP), 2025)
This article examines the application of the Cultural Approach to Organizations in addressing stunting cases in Indonesia, focusing on five regions with high prevalence: East Nusa Tenggara, West Sulawesi, Papua, West Papua, and Central Kalimantan. Using a qualitative method that integrates literature review, field observations, and interviews reported in prior studies, the research identifies how local cultural beliefs, traditional rituals, and social norms significantly shape child nutrition and health practices. The findings reveal that early introduction of solid foods, gender-based decision-making, and symbolic food rituals often conflict with recommended health guidelines, contributing to persistent stunting. The study highlights the need for culturally grounded interventions, recommending strategies such as community-based education, involvement of religious and community leaders, culturally adapted nutrition programs, improved healthcare logistics, and multisectoral collaboration. By aligning health initiatives with local cultural systems—including shared meanings, symbols, stories, and rituals—interventions are more likely to be accepted and sustained by local communities. This article contributes both theoretically to the development of the Cultural Approach in public health contexts and practically to policy design for culturally appropriate stunting prevention programs. The study recommends a strategic, inclusive framework to reduce stunting rates by integrating cultural understanding into public health communication and implementation.